2007
DOI: 10.1590/s1677-54492007000100014
|View full text |Cite
|
Sign up to set email alerts
|

Complicação vascular de osteocondroma: relato de caso

Abstract: Osteocondromas ou exostoses são os tumores benignos mais comuns do tecido ósseo. Eles surgem durante o período de crescimento e, raramente, são responsáveis por complicações vasculares. No presente relato, reportamos um caso de paciente com osteocondroma no membro inferior e complicação vascular provocada pela compressão da artéria poplítea. O paciente apresentava queixas de dor em membro inferior direito quando foi investigado com angiografia e radiografia, que identificaram a lesão vascular e a tumoração óss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In around 90% of cases they are single lesions. The appearance of multiple lesions is linked with an autosomal dominant pattern of heredity and it has been recently demonstrated that the EXT1, EXT2 and EXT3 genes are involved in its etiology [1][2][3][4][5] . Osteochondromas are composed of hyperplastic bone tissue provoked by abnormal development of subperiosteal epiphyseal cartilage, which gives the lesion a "protective cap".…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In around 90% of cases they are single lesions. The appearance of multiple lesions is linked with an autosomal dominant pattern of heredity and it has been recently demonstrated that the EXT1, EXT2 and EXT3 genes are involved in its etiology [1][2][3][4][5] . Osteochondromas are composed of hyperplastic bone tissue provoked by abnormal development of subperiosteal epiphyseal cartilage, which gives the lesion a "protective cap".…”
Section: Discussionmentioning
confidence: 99%
“…The tibia, fibula and humerus are the next most commonly observed sites, in decreasing order of frequency 2 . Osteochondroma rarely present with vascular complications and arterial lesions are more common of those that do have vascular involvement, accounting for 91%, with pseudoaneurysm the most often described of these, in 64% of cases 3,6 . The popliteal artery is most often affected because of the increased incidence of these lesions on the distal femur and proximal tibia and because of the artery's intimate relationship with the bone structure, since the artery is fixed proximally at the adductor canal by musculofascial compression and distally by its collateral branchings [1][2][3][4]6,7 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations